2010
DOI: 10.1021/ef100363c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Temperature on the Composition of Lignin Pyrolysis Products

Abstract: The temperature dependence of the pyrolysis products of two types of lignin (Alcell lignin and Asian lignin) was investigated using pyrolysis−gas chromatography−mass spectrometry (PyGC−MS). About 50 compounds were identified and quantified for each type of lignin over a temperature range of 400−800 °C. The maximum yield of phenolic compounds was obtained at 600 °C for both lignins, which was 17.2% for Alcell lignin and 15.5% for Asian lignin. Most of the phenolic compounds had an individual yield of less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
194
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(204 citation statements)
references
References 21 publications
10
194
0
Order By: Relevance
“…Toledano et al (2014b) concluded that the formation of desaspidinol depends on the solvent utilized in the system. Jiang et al (2010) studied the composition of the lignin pyrolysis products at various temperatures (from 400 to 800 °C). Desaspidinol was detected in both Alcell lignin and Asian lignin pyrolysis products by pyrolysis GC-MS. As the temperature increased from 400 to 800 °C, the proportion of desaspidinol decreased from 0.555 wt.% to 0.275 wt.% in the Alcell lignin pyrolysis vapor, and from 0.134 wt.% to 0.038 wt.% in the Asian lignin pyrolysis vapor (Jiang et al 2010).…”
Section: Compounds Of Depolymerization Products Identified By Gc-msmentioning
confidence: 99%
See 3 more Smart Citations
“…Toledano et al (2014b) concluded that the formation of desaspidinol depends on the solvent utilized in the system. Jiang et al (2010) studied the composition of the lignin pyrolysis products at various temperatures (from 400 to 800 °C). Desaspidinol was detected in both Alcell lignin and Asian lignin pyrolysis products by pyrolysis GC-MS. As the temperature increased from 400 to 800 °C, the proportion of desaspidinol decreased from 0.555 wt.% to 0.275 wt.% in the Alcell lignin pyrolysis vapor, and from 0.134 wt.% to 0.038 wt.% in the Asian lignin pyrolysis vapor (Jiang et al 2010).…”
Section: Compounds Of Depolymerization Products Identified By Gc-msmentioning
confidence: 99%
“…Jiang et al (2010) studied the composition of the lignin pyrolysis products at various temperatures (from 400 to 800 °C). Desaspidinol was detected in both Alcell lignin and Asian lignin pyrolysis products by pyrolysis GC-MS. As the temperature increased from 400 to 800 °C, the proportion of desaspidinol decreased from 0.555 wt.% to 0.275 wt.% in the Alcell lignin pyrolysis vapor, and from 0.134 wt.% to 0.038 wt.% in the Asian lignin pyrolysis vapor (Jiang et al 2010). Table 2 presents the Mw and Mn values, as well as the molecular weight distribution (Mw/Mn), of the depolymerization products.…”
Section: Compounds Of Depolymerization Products Identified By Gc-msmentioning
confidence: 99%
See 2 more Smart Citations
“…C-C bonds are the most stubborn bonds in lignin structures, and their cleavage only appears at high temperatures (Li et al 2015). Jiang et al (2010) studied the effect of temperature on the composition of lignin pyrolysis products and concluded that the maximum yield of phenolic compounds was obtained at 600 °C. However, pyrolysis oil obtained from the direct fast pyrolysis process also had some adverse properties, such as high acidity, high oxygen content, and the inherent complexity related to being a multicomponent mixture (Garcia-Perez et al 2007).…”
Section: Introductionmentioning
confidence: 99%